Detection of Formalin Content in Samples of Salted Fish in Traditional Market Sentra Antasari Banjarmasin - Safira Putri Nabilah; Muliyani Muliyani; Muhammad Zaini (UPPM Politeknik Unggulan Kalimantan, 2024)
Salted fish is a processed food product that is naturally preserved using salt, especially the people of South Kalimantan, there are concerns about the quality and safety of salted fish sold in the Banjarmasin area market. Based on the results of DKPP inspections (2018) in several traditional markets, namely Kuripan Market and Antasari Market, there are salted fish contaminated with formalin. This study aims to detect the percentage of salted fish with formalin in Banjarmasin's Sentra Antasari Traditional Market. This research is a quantitative descriptive study with observations using the random sampling method. The number of samples was 30 samples consisting of 5 types of fish consisting of salted squid, layang fish, selar kuning fish, peda fish and telang fish obtained from 6 different sellers. A total of 30 samples obtained 9 positive samples containing formalin which have been through the 0.1 N KMnO4 test and the Nash test which is accompanied by 3 replications of each test of 30 salted fish samples obtained 9 of which are positive for formalin. The results showed that the percentage of salted fish types that have formalin contamination is salted fish of layang type with a percentage of 50%, peda type fish, selar kuning and telang fish with a percentage of 33.33%. while salted squid has a percentage of 0% of the overall results showing the presence of 30% of samples containing formalin.